Predictors of Success of a Lifestyle Intervention in Relation to Weight Loss and Improvement in Glucose Tolerance Among Individuals at High Risk for Type 2 Diabetes - Nina Rautio; Jari Jokelainen; Timo Saaristo; Heikki Oksa; Sirkka Keinänen-Kiukaanniemi (SAGE Publishing, 2013)
Aim: The authors assessed the predictors of success of a lifestyle intervention (weight loss ≥ 5% and improved glucose tolerance) in individuals at high risk for type 2 diabetes in a 1-year follow-up in a primary health care setting. Methods: High-risk individuals for type 2 diabetes were identified by opportunistic screening in the implementation of the Finnish National Diabetes Prevention Program (FIN-D2D). All together, 3880 individuals participated in the 1-year follow-up. Sociodemographic characteristics, health status and behavior, family history of diabetes, clinical factors, and health care provider were considered possible predictors of lifestyle intervention success. Results: In sum, 19.3% of individuals lost at least 5% of weight, and 32.6% with abnormal glucose tolerance at baseline showed improvement in glucose tolerance. Abnormal glucose tolerance was the strongest predictor of weight loss and improvement in glucose tolerance. High attendance at lifestyle intervention visits, being outside of labor force, and high body mass index at baseline were also related to weight loss, and high education was related to improvement in glucose tolerance. Conclusions: In "real-life settings," glucose tolerance status, number of intervention visits, employment status, education, and body mass index explained the success of lifestyle intervention. These factors may help in targeting interventions, although they may not be generalized to other cultural settings.